2004
DOI: 10.1051/0004-6361:20031611
|View full text |Cite
|
Sign up to set email alerts
|

Penumbral structure at 0$\farcs$1 resolution

Abstract: Abstract.We analyse sunspot filtergrams of unprecedented quality obtained by Scharmer et al. (2002) with the Swedish 1-m Solar Telescope on La Palma. The observations comprise images in three different wavelength bands: 488, 436, and 430 nm (G-band). We find that there are still unresolved penumbral filaments which must have widths smaller than 80 km. The fine structuring along the filaments is limited. Penumbral grains have internal structure and look like they are split or crossed by narrow dark structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The sunspot penumbra is dominated by a small-scale structure, most prominently by the elongated bright and dark penumbral filaments, but also by the point-like penumbral grains, which have similarities to the umbral dots. At the highest currently reachable resolutions the bright penumbral filaments or fibrils show a sharp dark lane running inside them [215] and there is evidence that even these observations have not resolved all of the fine structure [216]. In the cores of spectral lines formed in the middle and upper photosphere this brightness modulation appears to be washed out or, at least, to be restricted to larger spatial scales [217].…”
Section: Brightness and Thermal Structuresmentioning
confidence: 99%
“…The sunspot penumbra is dominated by a small-scale structure, most prominently by the elongated bright and dark penumbral filaments, but also by the point-like penumbral grains, which have similarities to the umbral dots. At the highest currently reachable resolutions the bright penumbral filaments or fibrils show a sharp dark lane running inside them [215] and there is evidence that even these observations have not resolved all of the fine structure [216]. In the cores of spectral lines formed in the middle and upper photosphere this brightness modulation appears to be washed out or, at least, to be restricted to larger spatial scales [217].…”
Section: Brightness and Thermal Structuresmentioning
confidence: 99%
“…Sütterlin (2001), however, found an enhancement of spatial power at around 0.35 (250 km) and suggested that this was the preferred width of filaments. Observations with the new Swedish 1-m telescope (Rouppe van der Voort et al 2004), with spatial resolution of 0.12 (80 km), give a power spectrum that is not flat (it drops off roughly as k −4 , where k is the wavenumber), but also shows no distinct peak corresponding to a preferred width. This implies that there are unresolved filaments with widths less than 80 km.…”
Section: Penumbral Filaments and Grainsmentioning
confidence: 99%
“…The width of the grains is typically 0.5 (350 km) or less, and their lengths range from about 0.5 to 3.5 (350 to 2500 km). At the highest available resolution (see Figure 9), however, many of the bright filaments are seen to consist of several narrower components, some of which have lengths as great as 5 -9 (3500 to 6500 km) and thus can not properly be called grains (Rouppe van der Voort et al 2004). These observations also show that the most grain-like features are generally located at the end of the filaments nearest the umbra, and that these grains have internal structure with a few dark bands crossing them (as shown in Figure 9).…”
Section: Penumbral Filaments and Grainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Closer inspection of the bright filaments shows that they are composed of separate ‘penumbral grains’ (Muller 1973a,b), which have widths of 350 km or less, and lengths of around 350–2500 km. In addition, recent observations (Rouppe van der Voort, Löfdahl & Kiselman 2004) have found longer structures (3500–6500 km in length) and dark bands crossing many of the observed features. Scharmer et al (2002) report that bright filaments often have a dark lane running longitudinally down the centre.…”
Section: Introductionmentioning
confidence: 62%